Ukraine’s debt security in the context of military conflict - N. V. Pavlenko (Law and Safety)
In the context of military conflict, security issues come to the fore in all spheres of state life. As the combat capability of the army largely depends on the financing of its needs, the problem of finding additional financial resources is becoming more acute. However, the economy is currently unable to cope with this task due to the destruction of the material and technical base and logistics routes, military mobilisation of some employees, the outflow of labour resources abroad and other factors resulting from the armed aggression. Therefore, the search for ways to improve debt security in the context of a military conflict is of utmost importance.